2014
DOI: 10.1016/j.jacc.2014.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Electrocardiographic Anomalies in Young Individuals

Abstract: The study demonstrates that 1 in 5 young people have group 2 ECG patterns. The low incidence of SCD in young people suggests that in most instances such patterns are non-specific. These findings have significant implications on the feasibility and cost-effectiveness of nationwide screening programs for cardiovascular disease in young nonathletes and athletes alike, on the basis of current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 12 publications
1
34
2
1
Order By: Relevance
“…The prolonged QTc interval (>440 ms in males and >460 ms in females) was rarely found (0.03%). According to the same criteria, Basaravagajaiah et al 5 reported the prevalence of 0.4% in elite 7 comparing the prevalence of potentially abnormal ECG changes in young nonathletes and athletes found group 1 (training related) and group 2 (potentially pathological, training unrelated) patterns more prevalent in athletes. ECG patterns suggestive to ion-channelopathy or electrical heart disease were found in 13.5% of nonathletes and 16.4% of athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prolonged QTc interval (>440 ms in males and >460 ms in females) was rarely found (0.03%). According to the same criteria, Basaravagajaiah et al 5 reported the prevalence of 0.4% in elite 7 comparing the prevalence of potentially abnormal ECG changes in young nonathletes and athletes found group 1 (training related) and group 2 (potentially pathological, training unrelated) patterns more prevalent in athletes. ECG patterns suggestive to ion-channelopathy or electrical heart disease were found in 13.5% of nonathletes and 16.4% of athletes.…”
Section: Discussionmentioning
confidence: 99%
“…the duration of repolarization state. Prevalence of abnormal QTc interval duration reported by a numerous screening studies varied and ranged from very low 0.03% to over 6% [3][4][5][6] and for a combination of long and short QTc to over 16% in some studies, 7 due to age, sex, characteristics of the population studied-sport activity status, in particular, ethnicity, measurement technique, and criteria of cutoff points used by authors. The heart ratecorrected JT (JTc) interval has been proposed as a more appropriate measure of ventricular repolarization than the QTc interval in individuals with the increased QRS duration.…”
mentioning
confidence: 99%
“…Screening tests and their utility in competitive athletes were discussed by Leischik et al [20,21]. Following studies in athletes, a recent study also evaluated the usefulness of screening ECG in the general population [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, substantial electrocardiographic changes occur due to physiological changes from intense physical training 15 , and thus caution must be exercised when attempting to generalize these results to other populations. Nevertheless, it is clear from these cohorts that black athletes…”
Section: Discussionmentioning
confidence: 99%